spenito is required for sex determination in Drosophila melanogaster - Yan, Dong (Proc Natl Acad Sci U S A, 2015)
Sex-lethal (Sxl) encodes the master regulator of the sex determination pathway in Drosophila and acts by controlling sex identity in both soma and germ line. In females Sxl maintains its own expression by controlling the alternative splicing of its own mRNA. Here, we identify a novel sex determination gene, spenito (nito) that encodes a SPEN family protein. Loss of nito activity results in stem cell tumors in the female germ line as well as female-to-male somatic transformations. We show that Nito is a ubiquitous nuclear protein that controls the alternative splicing of the Sxl mRNA by interacting with Sxl protein and pre-mRNA, suggesting that it is directly involved in Sxl auto-regulation. Given that SPEN family proteins are frequently mutated in cancers, our results suggest that these factors might be implicated in tumorigenesis through splicing regulation.